Dynamics of quantum quadratic Volterra operators - Mukhamedov, Farrukh; Abduganiev, Abduaziz (2013)
In the present paper we introduce a new class of quantum quadratic operators which are called Volterra operators. We study dynamics of such kind of quadratic operators. Note that these operators act on the state space of the algebra of2 by 2 matrices